Application of laser-induced backscattering imaging system for classifying different ripening stages of Musa Acuminata cv. Berangan bananas - Zulkifli, Nurazwin (2017)
Inadequacy and inefficiency of monitoring quality systems for fruits have made a great impact that leads to an increasing number of post-harvest losses as they could have been damage during storage. Fruits undergone complex changes in their biochemical and physicochemical during ripening process. This study evaluates the potential of the backscattering imaging system to evaluate the bananas at different ripening stages. Backscattering image (BSI) of Musa Acuminata cv. Berangan was captured by a charge coupled device (CCD) camera and a laser diode emitting light at 658 nm. The system consisted of CCD camera with a zoom lens (focal length 18-108mm), a solid state laser diode of 658 nm at 1mm diameter as a light source and a computer equipped with an image processing software for automated image analysis. A total number of 360 samples of Musa Acuminata cv. Berangan from ripening stages 2 to 7 with 60 samples per stage group were used in this study. The gray level intensity and size of the backscattering area were used for estimating the quality properties of bananas. The results showed that the highest correlation was found between BSI parameters and total soluble solids content (TSS). Moreover, linear discriminant models were built for the two- class (unripe, ripe) and six-class (based on the commercial colour index) of ripening stages classifications. The overall accuracy for two-class and six-class classifications resulted in 94.2% and 59.2% classification accuracies, respectively. It can be concluded that the laser lightinduced backscattering imaging could be potentially used for predicting the ripening stages of bananas and could be further developed for an automated quality control system.